Smart agriculture – Urgent need of the day in developing countries - Goel, Raj Kumar; Yadav, Chandra Shekhar; Vishnoi, Shweta; Rastogi, Ritesh (Sustainable computing informatics and systems, 2021)
•Interconnection of agricultural systems with IoT & Big Data require AI to automate farming and provide rapid data analysis.•Society needs an adaptive agriculture that demonstrates resilience during future change.•The vital role of EO in monitoring, measuring and reporting progress towards achieving the SDGs document is also discussed.•Smart agriculture is the future of the food production sector as well as novel processes to confirm food safety of the world. Smart agriculture is based primarily on three platforms, namely science, innovation and space technologies. These are considered as the three pioneer pillars of nation building. Space technologies play a vital role in improving soil quality, reducing the waste of water during irrigation and sharing agricultural information with farmers. With the help of terrestrial, aquatic, and aerial sensors, satellites and surveillance equipment, a large volume of geo-spatial data from diversifying sources is collected, analyzed, and utilized for smart farming and shielding of crops. The technology foresight will introduce innovations such as the use of drones in agriculture, precision gene processing in plants, epigenetic, big data and internet of things (IoT), utilizing efficiently all types of energy like smart wind and solar energy, artificial intelligence-based application of robotics, desalination technology in mega-scale and so on. Some of these innovations are already being used in developed nations. Agriculture plays an important role in developing economy so the use of digital farming in rural areas will be a boon for agriculture sector. By 2030, 85% of the world's population is expected to live in developing countries. In this context, data-driven technological development is urgently needed for developing countries to increase gross domestic product (GDP) and ensure food security for the population.